2020
DOI: 10.1098/rspb.2020.1871
|View full text |Cite
|
Sign up to set email alerts
|

Personality composition determines social learning pathways within shoaling fish

Abstract: In shaping how individuals explore their environment and interact with others, personality may mediate both individual and social learning. Yet increasing evidence indicates that personality expression is contingent on social context, suggesting that group personality composition may be key in determining how individuals learn about their environment. Here, we used recovery latency following simulated predator attacks to identify Trinidadian guppies ( Poecilia reticulata ) that acted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
(85 reference statements)
0
11
0
Order By: Relevance
“…The reason for this high among‐shoal variation might be good nutrition status, which supports diversity in shoal‐level movement characteristics because of the complicated interactions among shoal members with a high degree of individuality. Previous studies found that the outcome of collective movement may be shaped by the personality composition (sometimes by the personality traits of one or several key individuals and sometimes by those of all group members) (Brown & Irving, 2014; Hasenjager et al ., 2020; Tang & Fu, 2019). Thus, if the shoals have more dominant members, the acceleration rate (as well as the swimming speed) might be faster because the collective movements change more.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this high among‐shoal variation might be good nutrition status, which supports diversity in shoal‐level movement characteristics because of the complicated interactions among shoal members with a high degree of individuality. Previous studies found that the outcome of collective movement may be shaped by the personality composition (sometimes by the personality traits of one or several key individuals and sometimes by those of all group members) (Brown & Irving, 2014; Hasenjager et al ., 2020; Tang & Fu, 2019). Thus, if the shoals have more dominant members, the acceleration rate (as well as the swimming speed) might be faster because the collective movements change more.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the outcome of the conflict between members with different nutritional statuses might depend on the personality type composition (more proactive and hence more dominant or vice versa ) of fed and starved fish. It has been reported that group‐level functions are related to personality composition (Hasenjager et al ., 2020). It is also possible that if the starved fish members are more dominant in any given heterogeneous group, there might be more fission and fusion episodes in that group or vice versa .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the extent that individuals use social learning can be dependent on group behavioral composition. For example, using network-based diffusion analysis it has been found that, in guppies, social learning rate is higher in both bold and risk averse individuals when they are part of groups dominated by risk-averse individuals or mixed groups and there is a bold demonstrator ( Hasenjager et al, 2020 ). Across gradients of environmental variation, among- and within-individual differences in behavioral expression in relation to performance curves may therefore lead to variation in social learning.…”
Section: Effects On the Costs And Benefits Of Groupingmentioning
confidence: 99%
“…In addition, the extent that individuals use social learning can be dependent on group behavioural composition. For example, using network-based diffusion analysis it has been found that, in guppies, social learning rate is higher in both bold and risk averse individuals when they are part of groups dominated by risk-averse individuals or mixed groups and there is a bold demonstrator (Hasenjager et al, 2020). Across gradients of environmental variation, among-and within-individual differences in behavioural expression in relation to performance curves may therefore lead to variation in social learning.…”
Section: Social Learning and The Spread Of Informationmentioning
confidence: 99%